Distribution patterns of Cuitlauzina pendula La Llave & Lex (Orchidaceae) over its phorophytes at the ‘Barranca de Cupatitzio’ National Park, in Uruapan, Michoacán, México - Pérez Decelis, Verónica A. (Universidad de Costa Rica, 2013)
.